Hypoxia-inducible factors enhance glutamate signaling in cancer cells - Hu, Hongxia (Oncotarget, 2014)
Signaling through glutamate receptors has been reported in human cancers, but the molecular mechanisms are not fully delineated. We report that in hepatocellular carcinoma and clear cell renal carcinoma cells, increased activity of hypoxia-inducible factors (HIFs) due to hypoxia or VHL loss-of-function, respectively, augmented release of glutamate, which was mediated by HIF-dependent expression of the SLC1A1 and SLC1A3 genes encoding glutamate transporters. In addition, HIFs coordinately regulated expression of the GRIA2 and GRIA3 genes, which encode glutamate receptors. Binding of glutamate to its receptors activated SRC family kinases and downstream pathways, which stimulated cancer cell proliferation, apoptosis resistance, migration and invasion in different cancer cell lines. Thus, coordinate regulation of glutamate transporters and receptors by HIFs was sufficient to activate key signal transduction pathways that promote cancer progression.